The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1108/md-03-2022-0407
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the feasibility of hyperlocal delivery model as an effective distribution channel

Abstract: PurposeThe successive waves of the Covid-19 SARS-II pandemic and the attendant lockdown imposed by the governments worldwide drove the economic activities to a halt. Offices and factories closed, production of goods and services declined and supply chains got severely disrupted. Many companies were embattled with the grim reality of shrinkage of aggregate demand, first due to supply shock and later due to loss of jobs and wages. Amidst all this, the handling and shipping of commodities became extremely complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…This could be due to the high initial investment and benefits over an extended period. The result parallels the earlier study of (Guru et al, 2023; Kapoor et al, 2014; Tapaninen et al, 2009), where OBS does not influence the usage of sustainable energy technology. Kapoor et al (2014), (Khan et al (2022) reviewed the literature systematically on innovation attributes of DOI theory and found that OBS does not influence solar energy adoption.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This could be due to the high initial investment and benefits over an extended period. The result parallels the earlier study of (Guru et al, 2023; Kapoor et al, 2014; Tapaninen et al, 2009), where OBS does not influence the usage of sustainable energy technology. Kapoor et al (2014), (Khan et al (2022) reviewed the literature systematically on innovation attributes of DOI theory and found that OBS does not influence solar energy adoption.…”
Section: Resultssupporting
confidence: 90%
“…This could be due to the high initial investment and benefits over an extended period. The result parallels the earlier study of (Guru et al, 2023;Tapaninen et al, 2009),…”
Section: Resultssupporting
confidence: 90%
“…Industrial agglomeration is widespread worldwide. The challenges brought by the global supply chain disruption during the COVID-19 epidemic also led governments to attach importance to industry integration and agglomeration, thus promoting the industry’s resistance to external shocks (Guru et al 2023 ; Wang et al 2023 ). From existing literature, research on IC mainly focuses on discussing its positive and negative external impacts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, several studies reported analytical frameworks on the LNG importation portfolio to investigate the optimal strategies [ [21] , [22] , [23] , [24] ]. For producing companies, early market assessments facilitate deciding and planning production capacities, selling portfolios, and delivery plans [ [25] , [26] , [27] ]. The uncertainties associated with energy markets and the increased competition motivated researchers to investigate and assess optimal LNG export strategies [ [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%